2014
DOI: 10.1007/s12035-014-8796-4
|View full text |Cite
|
Sign up to set email alerts
|

The Upregulation of NR2A-Containing N-Methyl-d-Aspartate Receptor Function by Tyrosine Phosphorylation of Postsynaptic Density 95 Via Facilitating Src/Proline-Rich Tyrosine Kinase 2 Activation

Abstract: The activation of postsynaptic N-methyl-D-aspartate (NMDA) receptors is required for long-term potentiation (LTP) of synaptic transmission. Postsynaptic density 95 (PSD-95) serves as a scaffold protein that tethers NMDA receptor subunits, kinases, and signal molecules. Our previous study proves that PSD-95 is a substrate of Src/Fyn and identifies Y523 on PSD-95 as a principal phosphorylation site. In this paper, we try to define an involvement and molecular consequences of PSD-95 phosphorylation by Src in NMDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…1 C and D). Consistent with other in vivo studies [17] , these data showed distinct expression pattern of the GluN2A- and GluN2B- containing NMDA receptor after depolarization. However in this study, we are interested in the impact of this dynamic expression of GluN2A-containing NMDA receptor on excitotoxicity induced by depolarization thus we inhibited the increase of GluN2A with a formerly developed peptide, while the NMDA receptor non-selective antagonist APV was used as a comparing manipulation other than control treatment.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1 C and D). Consistent with other in vivo studies [17] , these data showed distinct expression pattern of the GluN2A- and GluN2B- containing NMDA receptor after depolarization. However in this study, we are interested in the impact of this dynamic expression of GluN2A-containing NMDA receptor on excitotoxicity induced by depolarization thus we inhibited the increase of GluN2A with a formerly developed peptide, while the NMDA receptor non-selective antagonist APV was used as a comparing manipulation other than control treatment.…”
Section: Resultssupporting
confidence: 92%
“…However the contribution of different subtypes of the NMDA receptor in oxidative stress was not clearly investigated. More importantly, Zhao et al, recently found that the depolarization of neurons during ischemia stroke would specifically up-regulate the GluN2A-containing NMDA receptors [17] , but whether this selective and dynamic regulation of the GluN2A-containing subtype potentiates neuronal protection or neuronal death is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Each type of GluN2, including GluN2A and GluN2B, exerts its function largely by associating with the postsynaptic density protein PSD-95. 44 Moreover, synaptophysin, a major resident of the synaptic vesicle membrane, relates closely with the packaging and storage of synaptic vesicles and release of neurotransmitters. 15,45 In the present study, the upregulation of NMDARs and AMPARs in the amygdala after CFA injection increased the excitatory transmission, which contributed to anxiety-like behaviors in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the functional deficit is likely to result from its combination with dysregulation of NMDA receptors and possibly other proteins. PSD-95 is phosphorylated by c-Abl and SFKs on several tyrosine residues, which can favour PSD-95 aggregation and GluN2A activation2845. Thus, there appears to be a reciprocal interaction between Pyk2 and PSD-95, each enhancing the function of the other, thereby directly and indirectly regulating NMDA receptors and PSD organization.…”
Section: Discussionmentioning
confidence: 99%